PENGARUH LITERASI KEUANGAN DAN PERSEPSI RISIKO TERHADAP MINAT INVESTASI DI SECURITIES CROWDFUNDING - Junan Akhirul Istiqomah; Ida Nurhayati (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
In the midst of the rapid growth of the digital world, Securities crowdfunding has emerged as a promising financing innovation, especially for MSMEs that have been constrained by access to capital. However, the growth rate of financiers has actually slowed down nationally starting in 2021. This phenomenon indicates the existence of obstacles that need to be studied further. This study aims to analyze and determine the effect of financial literacy and risk perception on investment interest in Securities crowdfunding. With a quantitative approach, data was collected from 100 respondents in the DKI Jakarta area who have experience investing in Securities crowdfunding. The results of the analysis show that financial literacy and risk perception have a positive and significant influence, both partially and simultaneously, on investment interest in Securities crowdfunding. Together, these two variables are able to explain 76.2% of the relationship between investment interest in Securities crowdfunding. This finding confirms that improving financial literacy and understanding of risk is not only important for potential investors, but also crucial for strengthening an inclusive and sustainable Securities crowdfunding ecosystem, as well as a real way out for MSMEs in obtaining access to funding.